2020
DOI: 10.1002/chem.202001368
|View full text |Cite
|
Sign up to set email alerts
|

Para‐Selective Cyanation of Arenes by H‐Bonded Template

Abstract: The significance of site selective functionalization stands upon the superior selectivity, easy synthesis and diverse product utility. In this work, we demonstrate the para‐selective introduction of versatile nitrile moiety, enabled by a detachable and reusable H‐bonded auxiliary. The methodology holds its efficiency irrespective of substrate electronic bias. The conspicuous shift in the step energetics was probed by both experimental and computational mechanistic tools, which heralds the inception of para‐deu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 117 publications
0
28
0
Order By: Relevance
“…In 2020, Maiti and co-workers reported a para-selective cyanation protocol using their previously developed 2nd gen- eration D-shaped template considering its enormous importance in synthetic chemistry, agrochemicals, and pharmaceuticals. 16 para-Cyanation of toluene derivative, 30a was delivered in 70% yield with 10:1 selectivity (para:others) in presence of Pd(OAc) 2 , Ac-Gly-OH, Ag 2 CO 3 hexafluoroisopropanol (HFIP) solvent and CuCN as cyanating reagent (Scheme 12). Substrate containing electronically distinct functional groups were well tolerated under the reaction conditions to deliver the desired compounds in good to excellent yield with synthetically acceptable selectivity.…”
Section: Palladium Catalyzed Methodsmentioning
confidence: 99%
“…In 2020, Maiti and co-workers reported a para-selective cyanation protocol using their previously developed 2nd gen- eration D-shaped template considering its enormous importance in synthetic chemistry, agrochemicals, and pharmaceuticals. 16 para-Cyanation of toluene derivative, 30a was delivered in 70% yield with 10:1 selectivity (para:others) in presence of Pd(OAc) 2 , Ac-Gly-OH, Ag 2 CO 3 hexafluoroisopropanol (HFIP) solvent and CuCN as cyanating reagent (Scheme 12). Substrate containing electronically distinct functional groups were well tolerated under the reaction conditions to deliver the desired compounds in good to excellent yield with synthetically acceptable selectivity.…”
Section: Palladium Catalyzed Methodsmentioning
confidence: 99%
“…[288] The resulting biphenyl moiety is turned into a benzyl bromide scaffold after bromination with N-bromosuccinimide with benzoyl peroxide presence. Then, the resulting 4'-(bromomethyl)-[1,1'-biphenyl]-2carbonitrile [291] or the 4'-(bromomethyl)-4,5-dimethoxy-[1,1'-biphenyl]-2-carbonitrile [292] is then treated with magnesium turnings and iodine to afford the corresponding Grignard reagent to react with diisopropylchlorosilane. This intermediate is then brominated with N-bromosuccinimide and subsequently coupled to the phenol substrate.…”
Section: 1silyl-bridged Directing Groupsmentioning
confidence: 99%
“…[291] Recently, Lu et al demonstrated a palladium-catalyzed para-selective cyanation of phenols in moderate yields. [292] Again, the choice of an electronrich template and HFIP as solvent was founded to crucial for this protocol (Scheme 59). [292] Gervorgyan group envisioned the usage of easily removable silanols for diverse traceless palladium-catalyzed ortho-diversification in phenols.…”
Section: 1silyl-bridged Directing Groupsmentioning
confidence: 99%
See 2 more Smart Citations